PERANAN PENEGAK HUKUM TERHADAP HAK CIPTA KARYA MUSIK DALAM BENTUK JUAL BELI VCD BAJAKAN DI KABUPATEN LABUHANBATU UTARA - Indra Kumalasari Munthe (Jurnal Ilmiah Advokasi, 2018)
The copyright protection of music released in VCD form is a royalty rights of the songwriter. Legislation on Intellectual Property Rights is stipulated in the Copyright Act Number 28 of 2014. Piracy is the Unauthorized Copy of Works and / or Related Rights products and the distribution of such multiplication products widely to obtain economic benefits. The role of law enforcement in Labuhanbatu Utara District is needed to protect the copyrights of music works, however, the police officers never conduct regular raids against pirated dealers and sellers of VCDs. There are many actors who influence the rampant dealer and the sale of pirated VCDs in Labuhanbatu Utara Regency is a factor of law enforcement officers and community factors who prefer to buy pirated VCDs than the original VCD because the price is cheaper.Keywords: Copyright, Musical Works, Pirated VCDs